Representation of Women in Public and Private Spheres in Henrik Ibsen’s A Doll’s House - Puspita, Rani; Samanik, Samanik; Maretha , Carla (Kajian Linguistik dan Sastra, 2025)
This study examines Henrik Ibsen’s A Doll’s House through feminist frameworks, focusing on Nora’s navigation of 19th-century Norway’s public and private spheres. Using Simone de Beauvoir’s concept of “the Other” and Judith Butler’s theory of performativity, the analysis reveals how patriarchal norms shaped Nora’s subjugation and ultimate rebellion. The study highlights the play’s enduring relevance in advocating for gender equality and contributes to feminist literary criticism by exploring the intersection of gender, power, and societal norms. While previous studies have extensively analyzed Nora's character, this study explores how the play's portrayal of the duality of public and private spaces shapes Nora's rebellion against societal expectations. Furthermore, this study explores how Ibsen's work continues to resonate with contemporary audiences, highlighting the enduring relevance of his critique of gender inequality and the need for women's empowerment. By examining the enduring power of A Doll's House, the article argues that Ibsen's play continues to serve as a vital tool for understanding and challenging the structures that perpetuate gender inequality in the modern world. Abstrak Penelitian ini membahas drama Henrik Ibsen, Rumah Boneka, dari sudut pandang feminis. Kita akan melihat bagaimana Nora berjuang di tengah-tengah kehidupan publik dan pribadi di Norwegia abad ke-19. Dengan menggunakan konsep "The Other" dari Simone de Beauvoir dan teori performativitas Judith Butler, kita akan memahami bagaimana norma-norma patriarki menekan Nora dan akhirnya memicu pemberontakannya.  Penelitian ini menunjukkan betapa pentingnya drama ini dalam memperjuangkan kesetaraan gender, dan menambah wawasan kritik sastra feminis dengan melihat hubungan antara gender, kekuasaan, dan norma-norma sosial. Meskipun sudah banyak penelitian yang membahas karakter Nora, penelitian ini berfokus pada bagaimana penggambaran kehidupan publik dan pribadi dalam drama tersebut memengaruhi pemberontakan Nora terhadap harapan masyarakat. Penelitian ini juga akan mengeksplorasi bagaimana karya Ibsen masih relevan bagi penonton modern, menekankan kritiknya yang terus aktual tentang ketidaksetaraan gender dan pentingnya pemberdayaan perempuan. Dengan melihat dampak Rumah Boneka yang terus berlanjut, penelitian ini berpendapat bahwa drama Ibsen tetap menjadi alat yang ampuh untuk memahami dan menantang sistem yang menyebabkan ketidaksetaraan gender hingga saat ini.